2016
DOI: 10.1021/acsami.6b13416
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Redox Reactions Associated Ionic Transport in Oxide-Based Memories

Abstract: As an alternative to transistor-based flash memories, redox reactions mediated resistive switches are considered as the most promising next-generation nonvolatile memories that combine the advantages of a simple metal/solid electrolyte (insulator)/metal structure, high scalability, low power consumption, and fast processing. For cation-based memories, the unavailability of in-built mobile cations in many solid electrolytes/insulators (e.g., TaO, SiO, etc.) instigates the essential role of absorbed water in fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Mechanism of resistive switching in ECM systems is well understood under the oxidation of active electrode, migration of the mobile ions in solid electrolyte and their reduction at inert electrode which finally results in formation of a conductive filament between the two electrodes. Rupture and formation of this conductive filament under bias voltage is the major key in resistance switching . Therefore Redox reactions at the interface of solid electrolyte and metal electrodes play a vital role in ECMs.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Mechanism of resistive switching in ECM systems is well understood under the oxidation of active electrode, migration of the mobile ions in solid electrolyte and their reduction at inert electrode which finally results in formation of a conductive filament between the two electrodes. Rupture and formation of this conductive filament under bias voltage is the major key in resistance switching . Therefore Redox reactions at the interface of solid electrolyte and metal electrodes play a vital role in ECMs.…”
mentioning
confidence: 99%
“…Another study in Cu,Ag/Ta 2 O 5 /Pt cell has shown that using CV curves could reveal the effect of density on diffusion and filament growth of Ag and Cu. Also the effects originating from environmental condition, like moisture in the air, can be revealed using CV curves . Ag is the most promising candidate for use in ECM cells because of its high ion mobility and desirable electrochemical properties.…”
mentioning
confidence: 99%
See 3 more Smart Citations